Numerical investigation on I-beam to CHS column connections equipped with NiTi shape memory alloy and steel tendons under cyclic loads. (November 2015) - Wang, Wei; Chan, Tak-Ming; Shao, Hongliang
Abstract: This paper presents a numerical investigation on the energy dissipative and recentering behavior of I-beam to CHS column connections equipped with NiTi shape memory alloy (SMA) and steel tendons under cyclic loads. The finite element methodology has been validated against the companion experimental investigation. Numerical results have captured successfully the experimental observations including the load-deformation history and failure mode. Based on the validated finite element methodology, parametric analysis has been conducted to investigate the influence of the initial prestress and the geometric arrangement of the SMA tendons. Results indicated that by increasing the tendons' initial prestress, the connection's initial stiffness and energy dissipative performance increase. Under the same drift level, connection equipped with shorter tendons displayed higher energy dissipation while connection with the SMA tendons located outside the beam flanges showed higher energy dissipation.